The Influence of Social Media Sites Toward English Language Skills of English Departement Students at Sintuwu Maroso University - Molodu, Deby Asti; Modjanggo, Vivin Krismawanti; Patau, Sartika Andi (Sintuwu Maroso Journal of English Teaching, 2024)
This research aims to find out the nost common of social media sites that can influence on students’ English language skills and to determine the influence of social media sites toward English language skills of English Departement students at Sintuwu Maroso University. The method uses in this research is quantitative research with a survey design. Data is collected from questionnaire. 69 respondents are participated in filling out the questionnaire. Meanwhile, data is analysed uses SPSS version 25. The results of the research show that: 1) YouTube is the most common social media sites that can influence students’ English language skills as much as 68.1%, and 2) The influence of social media sites on students’ Eenglish language skills is 74.53%. It can be seen from the average value of the indicators, namely the easeof using social media sites (4.19), the influence of Instagram on writing skills (3.40) and reading skills (3.56), the influence of Facebook on writing skills (3.41) and reading skills (3.48), the influence of YouTube on listening and speaking skills (4.32), the positive influence of using social media sites in English learning (4.34). incorporation of social media sites in English learning (4.00), and the negative influence of using social media sites in English learning (2.90)